HUMAN ORGANIC SOLUTE TRANSPORTERS UTTERED IN SMALL INTESTINE, LIVER, AND KIDNEY FOR HOMEOSTASIS - CHINTHAGINJALA, HARANATH; AHAD, HINDUSTAN ABDUL; CHALLA, MAHESH REDDY; BARGHAV, GANDLA CHAITHANYA; DEVIKA, PASAM; VIKAS, SRIKANTHAM SAI (International Journal of Applied Pharmaceutics, 2019)
The transporters participate in a significant role in drug absorption, distribution, metabolism, and elimination. Transporters are of efflux and influx type, need ATP-binding sites for their in and out movement across the cell membrane. These transporters play an important role in allowing or opposing the drugs into the cells, results in non-linearity in drug pharmacokinetics. A wide range of transporters was discovered; among them, organic solute transporters (OST) play a key role in drug absorption and disposition. Organic solute transporters is a heteromeric transporter localized to the basolateral of epithelial cells. It is the primary efflux bile acid transporter in the intestine of mammals.